Cost effective robust rule calibration system. (2nd December 2014) - Greeff, P.; Kruger, O.
Abstract : One of the main calibration services of African NMIs (National Metrology Institutes) is the measurement of tapes and rules. This is mainly regulated by legal metrology and OIML (International Organisation of Legal Metrology) specifications are therefore referenced. Specifically, OIML R-35 is the standard to which rules or line scales must conform. The accuracy of most African NMIs systems however, cannot prove conformance to this specification. This article will detail the development of a new, cost effective, line scale calibration system, which will have accuracy better than the specification prescribed. The system was locally developed and its design is based on off-the-shelf components and open source software. It is also ready-for-upgrade to an absolute system. The system and details of the line detection algorithm will be presented.